The Effect of Realistic Mathematics Education in Enhancing Indonesian Students' Mathematical Reasoning Ability: A Meta-Analysis - Ariati, Chelsi; Juandi, Dadang; Hasanah, Aan; Suparman, Suparman (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Many researchers have carried out meta-analysis studies related to realistic mathematics education (RME) to enhance mathematical ability. However, their research does not focus on mathematical reasoning ability (MRA). This study aims to estimate and examine the effect of RME implementation in enhancing the MRA of Indonesian students, as well as to explore the moderating factors that influence students' heterogeneous MRA. The meta-analysis examined twenty-five relevant primary research published in national and international journals and sessions between 2010 and 2022. The steps of this research are formulate the problem, inclusion criteria, literature search strategy, study selection, data extraction, statistics analysis, interpretation and reporting. To calculate the effect size, the analytical tool employed the Comprehensive Meta-Analysis (CMA) program using the Hedge formula. Based on the random effect model, the total RME implementation had a very high effect (g = 1,064; p<0,05), significantly enhancing the MRA of Indonesian students. Furthermore, class capacity, educational level, and technological assistance did not influence students' heterogeneous MRA in the RME. These findings imply that Indonesian math educators should consider RME as one of the best ways to implement mathematics learning in the classroom to enhance students' MRA.